Матеріали до «Словника граматичного керування дієслів» - Колібаба, Л. (Лексикографічний бюлетень, 2011)
The article is devoted to theoretical bases and principles of compilation of the first modern Ukrainian linguistic Dictionary of grammatical government of verbs. The structure of vocabulary entries is thoroughly described. The specimens of the vocabulary entries of grammatical government of verbs are offered.